WEB BASED APPLICATION FOR BOARDING HOUSE SERVICE IN EKASAKTI UNIVERSITY AREA - Mulya Arta .S, Robert; Siregar , M. Ilham A (Jurnal Manajemen Teknologi Informatika, 2024)
A boarding house is one of the accommodation service providers or temporary residences consisting of several rooms, each room has facilities that have been provided by the owner of the boarding house. Searching for student boarding houses takes quite a long time and costs more to find a boarding house that suits your needs. To find information on boarding houses, students usually visit boarding houses between houses, ask local people who are close to the campus, walk around the campus and read advertisements in the mass media. The system development method used in making this final project uses the SDLC waterfall which consists of Planning, Analysis, Design and Implementation, with UML design tools consisting of Usecase Diagrams, Class Diagrams, Activity Diagrams and Sequence diagrams. In making this information system the author uses the PHP programming language, with MySQL database. This research produces a boarding house service application that can make it easier for students to search for and rent boarding houses in the Ekasakti University area. By using this information system, it is hoped that students will be helped in searching for boarding houses, because there are boarding house locations connected to Google Maps in the information system and students can make rentals, without having to directly meet the owner to make transactions, as well as several other menus. Web-based boarding house service application, which can solve the problem of difficulties for students in finding temporary housing such as boarding houses, using the SDLC development method, PHP programming language and MySQL database.